2019
DOI: 10.1152/ajpendo.00237.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity and exercise on colon cancer induction and hematopoiesis in mice

Abstract: Obesity-induced inflammation is associated with increased risk for colorectal cancer (CRC). The role of diet and exercise in modulating increased CRC risk in obesity and the potential role of altered hematopoiesis as a contributor to these effects remain unknown. The purpose of this study was to examine how weight loss induced during CRC induction with or without exercise alters CRC initiation and its relationship to altered hematopoiesis. Mice consumed either a control (CON) or a high-fat diet to induce obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The authors concluded that exercise, in a dose-dependent manner, abolished the deleterious effects induced by obesity and also inferred that this positive outcome was modulated by the adipokine secretion (adiponectin and leptin) profile and adiponectin receptor 1 enhanced expression, that in turn, act on cell cycle inhibition [159]. Another study evaluated the cessation of a high fat diet, followed or not by exercise, on colon rectal cancer risk and the authors concluded that the positive effect of exercise was mediated by lowering inflammation to a similar level found on control animals that have never been obese before [160].…”
Section: Studies In Animalsmentioning
confidence: 97%
“…The authors concluded that exercise, in a dose-dependent manner, abolished the deleterious effects induced by obesity and also inferred that this positive outcome was modulated by the adipokine secretion (adiponectin and leptin) profile and adiponectin receptor 1 enhanced expression, that in turn, act on cell cycle inhibition [159]. Another study evaluated the cessation of a high fat diet, followed or not by exercise, on colon rectal cancer risk and the authors concluded that the positive effect of exercise was mediated by lowering inflammation to a similar level found on control animals that have never been obese before [160].…”
Section: Studies In Animalsmentioning
confidence: 97%
“… 72 Even following subsequent weight loss, the chronic inflammatory state placed on the HSC niche leads to the accumulation of myeloid progenitors and LT- and ST-HSC depletion. 4 , 73 , 74 However, exercise mitigates these alterations in HSC activity. Circulating HSC concentrations have a noted increase following acute and endurance exercise training in mice.…”
Section: Bone Marrow—obesity and Exercise’s Effects On Bone Marrow St...mentioning
confidence: 99%
“… 81 Furthermore, exercise training in previously obese mice who had undergone weight loss and were at increased risk of carcinogenesis restored the HSC frequency to levels in never obese mice. 4 Thus, the effects of exercise appear to be dependent on exercise dose and model in healthy conditions and to reduce aberrant HSC expansion in disease.…”
Section: Bone Marrow—obesity and Exercise’s Effects On Bone Marrow St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise attenuates the production of leptin in adipose tissue, which in turn enhances CXCL12, a quiescence-promoting hematopoietic niche factor important in the maintenance of HSC function [102••]. In a separate study, mice fed a high-fat diet without exercise showed increased common myeloid progenitor cells and BM inflammation [103]. Overall, these studies indicate that exercise maintains HSC function by decreasing inflammation within the BM niche.…”
Section: Exercisementioning
confidence: 99%